SUBJEK AGRARIA PADA LOKASI KONFLIK KAWASAN TRANSMIGRASI (STUDI KASUS: UNIT PEMUKIMAN TRANSMIGRASI ARONGO, KABUPATEN KONAWE SELATAN) - Aryuni Salpianja Jabar; Danial Danial; Albasri Albasri; Yoenita Djayadisastra; Wa Ode Lusianai; Amin Tunda (Journal Publicuho, 2019)
The presence of an agrarian reform program in the current administration provides new hope for the management of more prosperous agricultural land, not least on transmigration lands. Especially in the determination of the Land of Agrarian Reform Objects (TORA) transmigration land received a share of 0.6 million hectares from 9 million hectares of the government's target. Unfortunately, until now there are still many images of transmigration lands that are far from expectations. This means that there are still many transmigration lands involved in conflicts both vertically and horizontally. This paper aims to analyze conflicts on transmigration lands located in UPT. Arongo, South Konawe Regency, Southeast Sulawesi Province. Conflict analysis is directed at mapping agrarian subjects involved in a conflict. Qualitative descriptive methods are used to obtain in-depth information related to the agrarian subject. The results showed conflict in the UPT transmigration land. Arongo consists of 3 agrarian subjects namely elements of government, private and community. The government element is represented by the local government, transmigration service and National Land Agency. Community elements consist of local residents, migrants who are not directly affected and transmigrants whose land is directly affected. Community elements were also formed within the United Farmers Konawe Selatan and Konsorsium Pembaruan Agraria (KPA). While PT. Merbau Jaya Indah Raya Group is part of the agrarian subject of the private element.